Διερεύνηση κριτηρίων χωροθέτησης και περιβαλλοντικών επιπτώσεων από την κατασκευή αγωγού φυσικού αερίου υψηλής πίεσης από την Κόρινθο (Εξαμίλια) έως την ΒΙ.ΠΕ. Πατρών - Ασκαρίδης, Νεόφυτος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών, 2015)
The necessity to give up conventional fuels, which are more expensive and detrimental to the environment, led the consumers to the use of a new, friendly and cheaper fuel, the natural gas. The use of natural gas is expanding at global scale; likewise in Greece the networks are continuously being extended in order to supply fuel to larger and larger parts of the country. This friendly fuel is supplied to the consumers through mainly underground piping networks, which constitute a part of public utility networks, such as roads, water supply, telecommunications networks etc.